THE INFLUENCE OF PERCEIVED VALUE ON SATISFACTION IN E-HAILING SERVICES: TIME AS MODERATING EFFECT - Emily H.T. Yapp; Jasmine A.L. Yeap, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
In the last couple of years, Millennials have emerged as the largest user segment of e-hailing services. Although e-hailing services have prospered, there is not much research that fully explores Millennial users’ satisfaction, particularly on e-hailing services. One of the most influential factors leading to users’ satisfaction in e-hailing services is perceived value. The purpose of this study is to determine the aspects of perceived value (economic value, convenience value, symbolic value, sustainability value and hedonic value) that lead to users’ satisfaction and whether time availability moderates the relationship between convenience value and satisfaction. The Partial Least Squares analysis on the data collected from 493 Millennials revealed that economic value, convenience value, sustainability value and hedonic value had a significant impact on satisfaction but not symbolic value. Interestingly, time availability was not found to moderate the relationship between convenience value and satisfaction. The findings are duly discussed in this paper.